Disentangling metabolic pathways involved in copper resistance in Candida fukuyamaensis RCL-3 indigenous yeast - Irazusta, Verónica Patricia (2015)
Candida fukuyamaensis RCL-3 yeast strain isolated from a copper filter plant is able to lower copper concentration in culture medium. In the present study, effect of copper in proteins expression and mechanisms involved in copper resistance were explored using comparative proteomics. Mono-dimensional gel electrophoresis revealed differential band expressions between cells grown with or without copper. 2-DE analysis of C. fukuyamaensis RCL-3 revealed that copper exposure produced at least an over-expression of 40 proteins. Sixteen proteins were identified and grouped in four categories according to their functions: glycolysis and ATP production, synthesis of proteins, oxidative stress response, and processing and transport of proteins. Integral membrane proteins and membrane-associated proteins were analyzed, showing nine protein bands overexpressed in Cu-supplemented medium. Four proteins were identified, namely nucleoporin pom152, elongation factor 2, copper chaperone Sod1 Ccs1, and eiosome component Lsp1. The proteomic analysis performed allowed the identification of different metabolic pathways and certain proteins involved in metal input and storage related to cell ability to bioremediate copper. These proteins and mechanisms could be used for future applications of C. fukuyamaensis RCL-3 in biotechnological processes such as remediation of heavy metals.